COMPARISON OF S.T.O.N.E. SCORE AND GUY SCORE IN PREDICTING STONE FREE RATES OF PERCUTANEOUS NEPHROLITHOTOMY PROCEDURES IN THE SOETOMO GENERAL HOSPITAL - I Dewa Gede Reza Sanjaya; Doddy M. Soebadi; Djojodimedjo, Tarmono; Bambang Soeprijanto (Indonesian Urological Association, 2021)
Objective: To determine the effectiveness of Modified Guy's Stone Score (GSS) and S.T.O.N.E score (SS) as predictors of stone free rates in patients undergoing PCNL. Material & Methods: The design of this study was a prospective observational analytic. Samples were patients with kidney stones who came to the Urology Polyclinic of Soetomo0 General Hospital Surabaya, which was planned to undergo PCNL surgery, patients who met the inclusion criteria will have a CT stonographic examination then counted for the S.T.O.N.E score and Modified Guy's Stone Score before the PCNL procedure. Postoperative stone size evaluation used KUB X-ray (BOF) to assess Stone Free Rate (SFR). Results: In the ETA statistical test there was a strong relationship between GSS and SFR with a relationship strength value of 0.609, the direction of the relationship between these two variables was positive. This means that the greater the GSS, the less likely the SFR could be achieved. The relationship between these two variables was significant with p= 0.05. While between SS and SFR with a relationship strength value of 0.55, the strength of the relationship in these two variables was positive which indicated the higher the SS, the less likely the occurrence of SFR. But both of them were not statistically significant with p= 0.228. Conclusion: Guy Stone Score (GSS) gives a better predictive value than the STONE score (SS) on the stone free rates in patients undergoing PCNL procedures.